An Analysis Of Expressive Speech Acts In The Dialogue Of Characters In Inside Out 2 - Yogia Natalia Simanjuntak; Lastri Wahyuni Manurung; Susanti Susanti (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2026)
This study analyzes the expressive speech acts used by the emotion characters in Inside Out 2. The objectives are to identify their types and to explain their functions in expressing emotions. Using a descriptive qualitative method and Searle’s speech act theory (1979), the data were taken from the characters’ dialogues. The results show twelve types of expressive speech acts: thanking, apologizing, congratulating, complaining, condoling, lamenting, protesting, deploring, praising, boasting, complimenting, and greeting. The most frequent is Praising (23 dialogues; 21.10%), followed by Complimenting (14 dialogues; 12.84%) and Boasting (11 dialogues; 10.9%). The least frequent is Deploring ( 3 dialogues; 2.75%). In conclusion, expressive speech acts in Inside Out 2 serve not only to express emotions but also to shape character development and storyline dynamics.